2021
DOI: 10.11604/pamj.2021.40.215.30159
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and etiologies of pulmonary hypertension at Somalia-Turkey Training and Research Hospital in Mogadishu

Abstract: Introduction pulmonary hypertension (PH) is one of the leading causes of mortality in the world. This study aimed to determine the ratio distribution and etiological characteristics of PH in Somalia-Turkey Training and Research Hospital. Methods the study was designed as a hospital-based retrospective observational study and included 260 patients who were diagnosed with PH by transthoracic echocardiography (TTE) in the cardiology outpatient clinic in Somalia-Turkey Trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
(30 reference statements)
1
0
0
Order By: Relevance
“…It is also lower than the prevalence reported in an earlier household-based cross-sectional study in Hargeisa (33.1%) [ 8 ]. Nevertheless, it is comparable to results from a similar study reported in a hospital-based cross-sectional study in Mogadishu city, Somalia (21.2%) [ 18 ], a systematic review on the prevalence of hypertension reported from Ethiopia (18.1%) [ 19 ], a WHO-STEP-wise approach survey in Kenya (24.5%) [ 20 ] and a pooled analysis of global data on hypertension (24.1%) [ 21 ]. However, direct comparison among these studies comes with a notable concern due to variations in the studied populations, settings, timing and duration of the studies and methodologies.…”
Section: Discussionsupporting
confidence: 89%
“…It is also lower than the prevalence reported in an earlier household-based cross-sectional study in Hargeisa (33.1%) [ 8 ]. Nevertheless, it is comparable to results from a similar study reported in a hospital-based cross-sectional study in Mogadishu city, Somalia (21.2%) [ 18 ], a systematic review on the prevalence of hypertension reported from Ethiopia (18.1%) [ 19 ], a WHO-STEP-wise approach survey in Kenya (24.5%) [ 20 ] and a pooled analysis of global data on hypertension (24.1%) [ 21 ]. However, direct comparison among these studies comes with a notable concern due to variations in the studied populations, settings, timing and duration of the studies and methodologies.…”
Section: Discussionsupporting
confidence: 89%